KONSEP RUSYANFIKR DAN IMPLIKASINYA BAGI PESANTREN GUNA MENCIPTAKAN KARAKTER REVOLUSIONER - Muhammad Nur Alam Tejo (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2017)
This article aims to explain Ali Shari'ati's concept about rusyanfikr. It is an idea that through pesantren a Kiai should be able to produce revolutionary Muslim intellectuals and he is supposed to be on the side of the oppressed ummah. This is possible because there is a patronage relation between a Kiai and his santris in which a Kiai has hegemony over the mindset of his santris. With strong patronage it is expected that a Kiai can encourage santris to become rusyanfikrs, that is, those who can find the truth in their community. Using the concept of rusyanfikr, it is expected that there is a new paradigm of how an intellectual should truly behave. As a central figure in the society, a Kiai has the same characteristics with a rusyanfikr, that is, someone who is born and grow in his'society’ so that a Kiai can no longer ignore the problems of his ummah.